THE EFFECT OF GENRE-BASED APPROACH ON IMPROVING SENIOR HIGH SCHOOL STUDENTS’ WRITING ABILITY ON NARRATIVE TEXT - Arundina Azzahra Mahendra; Afrianto; Dahnilsyah (International Journal of Educational Best Practices, 2025)
This study investigates the Genre-Based Approach (GBA) in improving the narrative writing performance of high school students. This study uses a pre-experimental pre-test-post-test design involving 30 eleventh-grade students from SMA Negeri 1 Pinggir. The intervention was implemented through four sessions following the stages of the Genre-Based Approach: Building Knowledge about the Field, Text Modeling, Joint Text Construction, and Independent Text Construction. Students' writing performance was evaluated in five components: content, organization, grammar, vocabulary, and mechanics, using an assessment rubric. The data were analyzed using the Shapiro Wilk test and paired sample t-test through SPSS version 26. The results revealed a statistically significant increase in students' writing scores (p = 0.000; t = -10.667), with the largest increase observed in content and vocabulary. These findings confirm that GBA effectively improves students' ability to generate and organize ideas coherently in the narrative genre. This study contributes to the growing body of research supporting process- and genre-based teaching in the context of English as a Foreign Language (EFL) and recommends the wider application of GBA in secondary school writing classes in the Indonesian Merdeka Curriculum.